Conservation and sustainability of turtle from the perspective of social science in Bakungan Kecil Island, Sandakan, Sabah, Malaysia - Ismail Ali; Mosli Tarsat; Encep Supriatna; Ma’ruf (Universitas Pendidikan Indonesia (UPI), 2023)
The writing of this paper aims to report on the results of research conducted on the conservation and sustainability of turtle in Bakungan Kecil Island in Sandakan, Sabah, Malaysia. Nowadays, turtles have been categorized as among the endangered species of life due to various factors. In fact, this study aims to find alternatives in the method of conserving and preserving turtle cubs from a social science perspective in addition to using existing methods of hatchery. The study began to be conducted for ten months from January to October 2022. The results from this study show that besides using the hatchery method there are three more methods that can be used in the conservation and sustainability of turtle, namely using cage, pond and tank method.